Evolution of Concept VIRTUAL PERSONALITY in Digital Age (a Sociolinguistic Study based on Russian Texts) - E. V. Marinova (Научный диалог)
The evolution of the concept of “virtual personality” relevant for the digital age (from diffuse to terminological) is considered. The means of its expression are analyzed. Research sources: personal websites and blogs of contemporary Russian authors, prose and philosophical texts. Electronic search databases were also involved: Russian National Corpus, the media bank “Integrum”. The objectives of the study are to define and describe the semantic structure of the term virtual personality; identify semantic connections with related nominations (network personality, digital personality; real personality); to establish possible transformations of the concept of “personality” in the digital age. The study was carried out using the methods of cognitive science and functional sociolinguistics. As a result: a model of a dictionary entry for the term virtual personality is presented (for the forthcoming dictionary of digital society terms). For the first time, a comparative analysis of the concepts of “virtual personality” and “digital personality” was carried out according to such criteria as intentional / unintentional, activity / passivity, subject / object of influence, presence / absence of (relative) freedom. A conclusion is proposed about the expansion of the semantics of the word personality in the context of digital technologies of the information society due to a new lexical-semantic variant: ‘a set of user data presented on the Web in digital format; digital footprint.